(untitled) (Konferensiyalar | Conferences, 2024)
This article delves into the process of Westernization in Uzbek literature during the Jadid era. It examines literary forms and genres from the 1980s, exploring their thematic content through the works of various writers and journalists. The conclusion emphasizes the goal of integrating Western thought with traditional Central Asian culture to promote social and cultural progress.